Penerapan Teknologi Kompor Oli Bekas dan Minyak Jelantah pada UMKM Tanaya di Kelurahan Sepinggan - Syahwaludin, Ahmad Zaki; Ariani, Misna; Rini, Listyo; Gunawan, Attila Ahmad; Maihani, Ersa; Windargani, Abdhie Surya; Fazly, Bhisma Azwardi; Telaumbanua, Elisandi Hosoloan; Natanael, Natanael; Aprizal, Saddam; Paskilla, Yasnina Novtria (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2025)
Used oil stove is one of the appropriate technologies that utilizes waste oil and cooking oil. In order to help MSMEs in Sepinggan Village, the B1A KKN XVI group of Balikpapan University designed a used oil stove work program. The purpose of the application of used oil and cooking oil stove technology is to help MSMEs to save expenses and utilize existing waste so as to obtain maximum profit with minimal production costs. In the application of used oil and cooking oil stove technology, there are two stages, namely: the preparation stage and the implementation stage. This work program produces appropriate technology that can increase the production of Tanaya MSMEs in Sepinggan Village so that it can increase income turnover and reduce fuel expenses because the potential of Tanaya MSMEs is very good to increase the value of the community's economic income.